MEGA YACHT, ITALIAN LEADERSHIP AND FINANCIAL CRISIS. EMPIRICAL EVIDENCE ON HOW ITALIAN LEADING COMPANIES IN MEGA YACHT SECTOR OVERCOME THE CRISIS - Merendino, Alessandro (European Scientific Journal, ESJ, 2014)
The current financial crisis is one of the most studied topics, which attracts the attention of many academics seeking to analyze its causes and impacts. Nevertheless many studies on this issue, the crisis effects on specific industries is still unexplored. The present research seeks to study this topic by analyzing the mega yacht sector with particular emphasis on two world leaders, i.e. Azimut-Benetti and Ferretti. The purpose of this study is to assess if they succeed to tackle the financial crisis, keeping a satisfactory level of profitability associated to a good financial health in spite of the financial crisis. Furthermore, we analyze the strategies those shipyards implement to survive the crisis. The concern of this research is both qualitative and quantitative. Hence, we calculate a complete set of financial ratios adopting a specific methodology for financial statement analysis, taking into account 2006-2013 financial years. That data is integrated with other information retrieved from companies annual report (i.e. the notes to the accounts, management reports and supervisory board reports). This study finds out that both companies suffer financial health and they do not register a satisfactory level of profitability, as well as a low rate of liquidly because of an excessive reliance on current liabilities. However, the key strategies to succeed are ongoing investments in state-of-the-art plant and machinery, an increasing use of equity (even though it is eroded by losses), along with steadily investments in R&D, trademarks, licenses and international nautical fairs.